2014
DOI: 10.1073/pnas.1409078111
|View full text |Cite|
|
Sign up to set email alerts
|

Uridine adenosine tetraphosphate is a novel neurogenic P2Y1 receptor activator in the gut

Abstract: www.pnas.org PNAS |

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
35
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(38 citation statements)
references
References 29 publications
(47 reference statements)
2
35
1
Order By: Relevance
“…Furthermore, vasoconstriction was observed in mouse renal arterioles (7) and aorta (8). Although, there is evidence that Up 4 A can produce vasodilation in isolated aortic rings of rats (5), porcine coronary small arteries (11, 12), human and mouse colon (30) as well as induce hypotension in conscious rats (8). All together, these studies suggest that the vascular responses to Up 4 A likely depend on the type of vascular beds and species studied (4).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, vasoconstriction was observed in mouse renal arterioles (7) and aorta (8). Although, there is evidence that Up 4 A can produce vasodilation in isolated aortic rings of rats (5), porcine coronary small arteries (11, 12), human and mouse colon (30) as well as induce hypotension in conscious rats (8). All together, these studies suggest that the vascular responses to Up 4 A likely depend on the type of vascular beds and species studied (4).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, Up 4 A induces vasoconstriction in rat perfused kidney through P2X 1 R and P2Y 1 R (10), in rat aorta through P1R and P2XR (5), and in rat pulmonary arteries through P2YR (6), while Up 4 A produces vasodilation in rat perfused kidney through P2Y 1 R and P2Y 2 R (10), in porcine coronary arteries through A 2A AR, P2X 1 R and P2Y 1 R (12) and in human and mouse colon through P2Y 1 R (30). Surprisingly, Up 4 A-mediated vascular contraction in mouse aorta in the present study was not affected by A 3 AR deletion, although one of our previous observations showed that activation of A 3 AR contributes to mouse aortic contraction (19).…”
Section: Discussionmentioning
confidence: 99%
“…A range of dinucleoside polyphosphates, from triphosphates to higher homologs, occurs naturally. For example, P 1 -(59-adenosinyl)-P 4 -(59-uridinyl)-tetraphosphate (Up 4 A) is released from the vascular endothelium to induce vasoconstriction and has been explored in various biologic contexts, such as P2Y 2 R-induced migration of smooth muscle cells and activation of enteric neuronal P2Y 1 R (Wiedon et al, 2012;Durnin et al, 2014). Diadenosine polyphosphates, such as Ap 4 A, are plentiful in platelet granules and secretory granules of nerve terminals.…”
Section: Introductionmentioning
confidence: 99%
“…Each of these has greater or lesser affinity for the different purine receptors subtypes (31). It was recently hypothesized that β-NAD (β-nicotinamide adenine dinucleotide), ADPR (ADP ribose) or Up4A (uridine adenosine tetraphosphate) might be (even instead of ATP) the purinergic neurotransmitter in the GI tract (46)(47)(48)(49). However, some experimental data have nuanced these results (43,50-52).…”
Section: Atp and Maybe Other Neurotransmitters?mentioning
confidence: 99%